The first steps of President Juan Rafael Mora Porras - de la Cruz de Lemos, Vladimir (2022)
Received: 13 de mayo de 2022.Approved: 02 de junio de 2022. Incorporation speech in the Costa Rican Morist Academy, as Number Academician, delivered on Tuesday, May 17, 2022, at the Union Club.